Book Review Manual of Chronic Total Occlusion Percutaneous Coronary Interventions: A Step-by-Step Approach - Sidhi Laksono (Berkala Ilmiah Kedokteran Duta Wacana, 2022)
The Manual of Chronic Total Occlusion Percutaneous Coronary Interventions: A Step-by-Step Approach, Third Edition is a useful reference for percutaneous coronary intervention (PCI) with chronic total occlusion (CTO). Written by national and international experts in the field of CTO and edited by Emmanuel Brilakis, this book gives the steps necessary to do CTO PCI, the pitfalls to watch out for, and how to modify tactics if we face CTO complications. This manual book is dedicated and made for interventional cardiologists, interventional cardiology fellows, general cardiology residents, also cardiac catheterization laboratory staff. This book will give you the latest state of the art in the field of CTO PCI. In this new edition, new numbers, images, and algorithms have been developed and shared to reflect the CTO PCI updates. Additionally, this update includes links to nearly 200 of his CTO PCI cases. The structure of the book has been completely revised to align with the recently published Manual of Percutaneous Coronary Intervention.